Analyzing cruise ship itineraries patterns and vessels diversity in ports of the European maritime region: A hierarchical clustering approach. (May 2020) - Vicente-Cera, Isaías; Acevedo-Merino, Asunción; Nebot, Enrique; López-Ramírez, Juan Antonio
Abstract: In this paper, European maritime cruise ship traffic of 1031 ports visited by 209 cruises is evaluated with different mathematical tools. Through an innovative ecological analogy, the diversity of ships in every port has been calculated using Simpson, Shannon, Margalef, and Berger-Parker diversity indexes and Automatic Identification System data from the cruise fleet in year 2015. By combining the results of Visiting Vessels Diversity with an Agglomerative Hierarchical Clustering analysis, five different homogeneous cruise regions were identified that match with those normally established by cruise ship associations. Classification trees techniques also demonstrated that cruise ships' diversity in a port could significantly predict these cruise regions with high levels of confidence. All of this information together can serve as an input to develop and improve economic and environmental strategies of cruise ports and their cities. The primary goal of this paper is to obtain a picture of the behaviour of cruise traffic in the European maritime region, grouping ports in clusters based on the absence or presence of cruise ship on those ports and determining the diversity of vessels in each port. Graphical abstract: Unlabelled Image Highlights: Diversity indexes prove to be very useful in defining the ships present in a port A cluster analysis of AIS data revealed that, five homogeneous cruise regions exist The diversity of the port is able to predict which cluster group it belongs to Statistical tools enlighten that there are patterns in the behavior of cruise routes